Intuitive Expertise in Moral Judgments. Issue 2 (3rd April 2022) - Horvath, Joachim; Wiegmann, Alex
ABSTRACT: According to the 'expertise defence', experimental findings suggesting that intuitive judgments about hypothetical cases are influenced by philosophically irrelevant factors do not undermine their evidential use in (moral) philosophy. This defence assumes that philosophical experts are unlikely to be influenced by irrelevant factors. We discuss relevant findings from experimental metaphilosophy that largely tell against this assumption. To advance the debate, we present the most comprehensive experimental study of intuitive expertise in ethics to date, which tests five well-known biases of judgment and decision-making among expert ethicists and laypeople. We found that even expert ethicists are affected by some of these biases, but also that they enjoy a slight advantage over laypeople in some cases. We discuss the implications of these results for the expertise defence, and conclude that they still do not support the defence as it is typically presented in (moral) philosophy.